A novel Schiff-base as a Cu(II) ion fluorescent sensor in aqueous solution - AYDIN URUCU, OYA (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
A new fluorescent Cu(II) sensor (L) obtained from the Schiff base of 5,5 '-methylene-bis-salicylaldehyde with amidol (2,4-diaminophenol) was synthesized and characterized by FT-IR, MS, H-1 NMR, C-13 NMR techniques. In the presence of pH 6.5 (KHPO4-Na2HPO4) buffer solutions, copper reacted with L to form a stable 2:1 complex. Fluorescence spectroscopic study showed that Schiff base is highly sensitive towards Cu(II) over other metal ions (K+, Na+, Al3+, Ni2+, Co2+, Fe3+, Zn2+, Pb2+) in DMSO/H2O (30%, v/v). The sensor L was successfully applied to the determination of copper in standard reference material. The structural properties and molecular orbitals of the complex formed between L and Cu2+ ions were also investigated using quantum chemical computations. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Chemosensor; Copper (II); Fluorescence; Schiff-base; TRANSITION-METAL-COMPLEXES; COPPER; CHEMOSENSOR; DISEASE; DESIGN; CU2+; DISORDERS; SWITCHES; ATPASES